Steam Consumption on Solvent Recovery Distillation of 1500t/a Propylene Oxide Pilot Plant: Simulation and Optimization - Li, Yi-Chuan; Shen, Ben-Xian; Xiao, Wei-Guo; Wang, Lei; Zhao, Ji-Gang (Asian Journal of Chemistry, 2013)
China's first pilot-scale hydrogen peroxide to propylene oxide (HPPO) plant has been built in Tianjin in March 2009. In the test duration, it produced qualified propylene oxide but its solvent recovery distillation consumed more energy. In order to improve the energy utilization level of plant, the solvent recovery process was simulated and its steam consumption was optimized by PRO/II with established thermodynamic model. According to the energy-saving optimization results, the actual steam consumption performed in the 1500 t/a plant could be reduced by 6.2 %.